PENGGUNAAN APLIKASI QUIZIZZ SEBAGAI METODE EVALUASI DALAM PEMBELAJARAN LITERASI TERHADAP HASIL BELAJAR SISWA KELAS 3 SDN SENDANGMULYO 02 SEMARANG - Rafika Nuriafuri; Sumarno; Ida Dwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Teachers should use comprehensive and sophisticated methods when conducting learning evaluations to stimulate students' curiosity and encourage critical thinking. Quizizz allows students to compete in a healthy way, increasing student engagement and improving learning outcomes. Students take the quiz with their class and see the rankings directly on the leaderboard. The researcher's goal is to help students understand the material by using the Quizizz application. The type of research used is descriptive qualitative with a phenomenological approach in the form of data collection carried out by means of observation, interviews and documentation. The results showed that the use of the Quizizz application can increase enthusiasm, curiosity and critical thinking as seen from the observations made by researchers obtained the highest score obtained 9. So thus the use of the Quizizz application has a high influence on the learning evaluation method in class III at SDN Sendangmulyo 02 Semarang.